Energy efficient resource allocation scheme for AF relay downlink system - Yu CHEN; Xu-ming FANG; Bo HUANG (Tongxin xuebao)
In order to maximize the total energy efficiency of amplify-and-forward relay downlink system,a joint scheme of relay selection and power allocation was proposed with the circuit power of the system.For reducing the computa-tional complexity,a step-by-step suboptimal allocation scheme was provided.Firstly,the virtual direct channel gains were adopted to select appropriate transmission link.Meanwhile,relay system was converted to the single hop system.Then,the power allocation could be solved by convex optimization.Besides,in order to accommodate different user distribu-tions,a resource allocation scheme based on cell zooming was also proposed.Simulations demonstrated that the solution of the proposed suboptimal scheme approaches the optimal solution.Additionally,the scheme with cell zooming is adaptable to different user distributions and further improves the total system energy efficiency.